A study on the image of public libraries as perceived by the local government officials and civil servants in the municipality of Rodriguez, Rizal - Evangelista, Pearly Ann P.
As mandated by Republic act No. 7743, “An Act Providing for the Establishment of Congressional, City and Municipal Libraries and Barangay Reading Centers Throughout the Philippines, Appropriating the Necessary Funds Therefor and for Other Purposes,” the local government of Rodriguez, Rizal is required to put up a public library and barangay reading centers in their respective areas.